Aesthetic Receptivity in Cirebon Mask Music: Analyzing the Correlation Between Rhythm and Motion - Irniatie Wanda; Sunarmi; Sarwanto (Jurnal Seni Musik, 2025)
This phenomenological study investigates the receptive aesthetics in the accompaniment music of Cirebon Mask Dance (Tari Topeng Cirebon), focusing on the perceptual dynamics of rhythmic beauty and percussive patterns and their intricate correlation with dance movements. Employing Interpretative Phenomenological Analysis (IPA) within a qualitative framework, this research explores how mask dancers and musicians interpret and respond to specific percussive patterns fundamental pulse, accented strike, and melodic-rhythmic ornamentation as complex aesthetic stimuli that fundamentally shape movement quality and character embodiment. The findings reveal a sophisticated audio-kinesthetic aesthetic system where beauty emerges from precise intersubjective synchronization between sonic impulses and kinetic energy release, mediated by culturally encoded bodily awareness and affective resonance. This study addresses a critical gap in existing literature by privileging insider (emic) perspectives often marginalized in structural and symbolic analyses. The research contributes to performance theory by proposing an integrated "audio kinesthetic receptive framework" and offers practical implications for culturally responsive pedagogy in traditional arts education, emphasizing the necessity of integrative dance and karawitan curricula to preserve the receptive sensitivity that constitutes the performative essence of this intangible cultural heritage